A Novel Inverter-Based MPPT in Grid-Connected PV Systems Using Sliding Mode Control with Moving Average and Chattering Mitigation - Caglayan, Ruhi Zafer; Coteli, Resul; Kayisli, Korhan (Institute of Electrical and Electronics Engineers Inc., 2025)
Renewable energy systems (RES) are important, and RES are connected to the system with DC/DC and DC/AC converters. This paper presents a novel inverterintegrated maximum power point tracking (MPPT) strategy for grid-connected photovoltaic (PV) systems, where no intermediate DC-DC converter is employed. The proposed method directly controls PV panels' voltage value using a sliding mode control (SMC) algorithm to achieve robust and fast convergence to the maximum power point under varying solar irradiance and adopts the DC voltage to the AC side. By integrating the MPPT process into the inverter stage, the system reduces the number of switching components, minimizes conversion losses, and improves overall efficiency. The stability and robustness of the SMC-based approach are analytically evaluated using a moving average method and reducing chattering with a suitable algorithm. Its performance is validated through simulation results. The findings demonstrate that the inverter-integrated SMCMPPT ensures accurate power tracking, stable grid synchronization, and enhanced dynamic response compared to a Sinusoidal Pulse Width Modulation-based system, making it a promising solution for next-generation PV grid integration. © 2025 IEEE.
14th International Conference on Renewable Energy Research and Applications, ICRERA 2025 -- 27 October 2025 through 30 October 2025 -- Vienna -- 219191
Keywords: AC/DC; Maximum Power Point Tracking (MPPT); Photovoltaic (PV); Pulse Width Modulation (PWM); Sliding Mode Control (SMC)